Studies on phyoremediation of copper using pteridium aquilinum (bracken fern) in the presence of biostimulants and bioassay using clarias gariepinus juveniles (2013)
A study was carried out to evaluate the uptake of copper from water containing 10 mg/L copper by Pteridium aquilinum (bracken fern) and Clarias gariepinus in the presence of five plant growth stimulants: Nitrogen: phosphorus: potassium (15-15-15: an inorganic fertilizer), pig, cattle, poultry, and a mixture of pig/cattle manures. A plant growth stimulant differentiated each treatment. A 96-hour bioassay using C. gariepinus was carried out at the end of the experiment to test the efficacy of the clean up by P. aquilinum. The control experiment contained no copper or plant growth stimulant. Fish survival, uptake of copper by P. aquilinum, C. gariepinus, concentration of copper in water, hematology and histopathology of the fish were assessed. Higher concentrations of copper were reported in P. aquilinum than in water or C. gariepinus. Low fish mortality was reported with the highest being 20% in the cattle manure-containing treatment. Low fish mortality was reported with the highest being 20 percent in the cattle manure containing treatment